Clinical pattern of acute pancreatitis in eastern India and comparison of Ranson, BISAP and APACHE II as a predictor of severity, local complications and mortality - Ekka, Nishith M. Paul; Mishra, Gaurav; Kumar, Vinod; Tiwary, Arun Kumar; Kar, Tanushree; Tiwary, Ashutosh (International Surgery Journal, 2018)
Background: Acute pancreatitis is the single most frequent gastrointestinal cause of hospital admissions. Scoring systems have been used since the 1970s for assessment of its severity. This study was aimed to assess the clinical pattern of acute pancreatitis and to compare various predicting systems like Ranson, BISAP and APACHE II in predicting severity, local complications and mortality in acute pancreatitis. Methods: In this prospective study, 91 consecutive cases of acute pancreatitis admitted, between April 2015 to March 2017, were studied. The diagnostic criteria include the presence of at least two of the three features; abdominal pain, serum amylase and lipase levels and findings on imaging studies. Patients were divided into two groups each, BISAP Ranson ≥3 and <3, APACHE II ≥8 and <8, and analyzed statistically. Results: Out of total of 91 patients, 81 were male and 14 were female with mean age was 36.14 years. Commonest aetiological factor was alcoholism in 57.89% followed by gallstones in 23.16%. Serum amylase was raised in 83.26% patients while 95.79% had raised serum lipase levels. 75.79% patients were of MAP while 24.21% patients were of MSAP and SAP. 7.37% patients developed local complications and mortality rate was 6.32%. All the scoring systems were found similar in predicting severity, local complication and mortality, had low sensitivity and high specificity (P value < 0.05). Conclusions: There is no ideal predicting system for acute pancreatitis. These scoring systems can be used to triage patients for better healthcare delivery.